THE EFFICIENCY OF TEACHING ENGLISH WITH USE OF GAME TECHNOLOGY - Murodillayeva Durdona Zafarjon qizi (World Scientific Research Journal, 2025)
Annotation: The role and importance of game technologies in the process of teaching English. This articles explores the game provides opportunities for students to increase their interest and motivation in the language, consolidate their knowledge, and develop their communication skills. Gamification provides ways to engage students in language learning, increase their motivation and make lessons interactive. Methodological approaches are examined through examples.